How can we manage cultural competence in mental health nursing? - Kleanthous, Efrosyni; Karanikola, Maria (My University, 2010)
Research evidence indicates that mental health nurses have limited awareness and knowledge about the care of culturally diverse people as well as deficiencies in education programmes in transcultural nursing. The article demonstrates fundamental differences of mental health nursing care in western and non-western societies. It also describes Leininger’s principles for transcultural mental health nursing as well as the application of Papadopoulos, Tilki and Taylor model for the development of mental health nurse’s cultural competence. The structural elements of this model are cultural awareness, cultural knowledge, cultural sensitivity and cultural competence.
Πως επιτυγχάνεται η πολιτισμική επάρκεια στη νοσηλευτική ψυχικής υγείας;
Keywords: Culturally diverse; Cultural awareness; Cultural knowledge; Cultural sensitivity; Cultural competence